A cross-sectional study to assess the prevalence of early childhood caries and associated risk factors in preschool children in district Mandi, Himachal Pradesh - K Sharma; K K Gupta; A Gaur; A K Sharma; V Pathania; V B Thakur (Wolters Kluwer Medknow Publications, 2019)
Aim: The aim of this cross-sectional study is to investigate the prevalence and related risk factors of early childhood caries (ECC) in preschool children of district Mandi, Himachal Pradesh, India. Materials and Methods: A total sample of 2859 children aged between 2 and 6 years were selected from various parts of district Mandi. The status of dental caries and decayed missing and filled teeth (DMFT) score was recorded. Results: ECC increased significantly with age. Boys had significantly higher caries prevalence and mean DMFT score as compared to girls. Children who belonged to low socioeconomic group showed higher caries prevalence and mean DMFT score. Children aged 3-6 years who brushed their teeth twice daily had the least prevalence of dental caries as well as DMFT score when compared to children with one time and no brushing. Conclusion: The early identification of poor oral hygiene and improper feeding habits should be considered in preventive health promotion in low socioeconomic communities of district Mandi, Himachal Pradesh.